A randomized controlled study on the effectiveness of a diabetes self-management app in Bangladesh - Bilkis Banu; Nasrin Akter; Sujana Haque Chowdhury; Nusrat Hossain Sheba; Md. Abdul Hakim Majumder (BioSocial Health Journal)
Introduction: The smart phone application concept is widely recognized as a tool to support patients’ adherence. Using different types of reminder-based materials combined with traditional health education has demonstrated its effectiveness in enhancing knowledge and fostering adherence to diabetes management. Very few studies found to identify the effectiveness of smartphone application for the diabetes seven self-management components. This study was aimed to assess this issue among Bangladeshi patients. Methods: A randomized controlled trial was performed from July 2022 to June 2023 in two diabetic hospitals affiliated with the Diabetic Association of Bangladesh located in Dhaka district among the 400 diabetic patients. The smartphone Application ‘Diabetes Self-Care’ was installed on the smartphone of each patient of the intervention group and instructed them to use it. Data were collected using a semi-structured questionnaire through face-to-face interview. Knowledge and adherence were measured and compared in the different groups before and after the intervention using t-test, McNemar’s test, and logistic regression technique. Results: The endline status of the intervention group reflected significant (P<0.01) improvement in knowledge and adherence to self-management compared to the baseline status. Knowledge (regarding seven self-management components, basic and technical components of diabetes) improved significantly (P<0.01) in the intervention group. Adherence to self-management components improved significantly(P<0.01) more in the intervention group than in the control group. Conclusions: The m-Health intervention, using smartphone application, demonstrated a noteworthy enhancement and positive impact on patients’ knowledge and adherence. This successful model of intervention holds the potential for nationwide replication, offering a viable approach for self-managing diabetes and other non-communicable diseases to enhance patient outcomes and reduce healthcare burdens.